Evaluating Construct Validity and Reliability of Work Family Strength (WFS) : Indonesia Women Leader Context - Dhini Rama Dhania (Journal of Educational, Health and Community Psychology, 2022)
The strategic role of leadership on organizational performance is the reason why this topic continues to be researched in research and practical studies. Female leaders in Indonesia are still faced with the problem of a narrow symbolic idealization perspective such as feeling it is impossible to achieve success in both the domestic and public fields, and also feeling guilty for violating. The nature of women Therefore, awareness of the power of work and family is important for female leaders because by creating positive feelings, individuals will have a broad perspective in influencing other roles and aspects of their lives. Work family strength (WFS) is a positive experience brought from work roles as well as roles in the family. For that we need a measurement related to work family strength (WFS). So far, research related to female leaders is more related to work family conflict, for this reason the research provides updates related to positive things, namely work family strength, especially in measuring tools. The absence of adaptation in other languages is deemed necessary to adapt the work family strength scale in Indonesian. Adaptation is carried out based on the guidelines for adapting measuring instruments from the International Test Commission (ITC), which includes a forward - backward translation process, followed by expert review to test language and conceptual equivalence. The validation process is carried out by testing content validity, through the Content Validity Index (CVI), and construct validity, using Confirmatory Factor Analysis (CFA). The trial was conducted on 300 female leaders who work in for-profit companies, who work more than 40 hours/week and have families (husbands or children). Based on this trial process, it is known that each indicator, dimension, and construct meets all the criteria for Goodness of Fit (RMSEA < 0.08; CFI > 0.9). In addition, the value of Construct Reliability (CR) > 0.70 and Average Variance Extracted (AVE) > 0.50 were also obtained. Thus, the work family strength scale can be used as a valid and reliable measuring tool.Â Keywords : Work Family Strengths, Women Leader, Confirmatory Factor Analysis